Enhance Knowing Thyself and Self-Development Based on Personality Types Through LKMM Implementation - Balan, John M; Lina, Virgilius Bate; Rato, Virgilia S. Gele; Bolet, Bernadus (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Getting to know and developing oneself is a task in every stage of human life development. Knowing and developing oneself into a potential individual, various approaches and methods should be used to achieve the goals. LKMM is one of the many approaches and ways to help students recognize and develop their own self potential. What does the abbreviation LKMM stand for? The abbreviation LKMM stands for the following characteristics: L (Latihan) K (Keterampilan) M (Manajemen) M (Mahasiswa) which means Students Skill Management Training (SSMT). The aim of this journal article is to re-mix the theme of "self-recognition and development" which is conducted in LKMM activities based on theories of self-recognition and self-development. Two methods are used to summarize this review, namely a literature review as a theoretical framework and a personality type assessment for volunteer participants and a lecturing method in three days LKMM activities. The results of the assessment and its interpretation supported by a lot of theories are presented in this review. The main elements discussed in this article are the essence of self, knowing thyself, and one's own potential, self-development, and LKMM as a training program and the guidelines of its implementation. This activity was held in collaboration with the HMPS PGSD committee and the Counseling Service Center and Campus Ministry of the University of Flores. The target group is third semester PGSD students at Flores University. The element of novelty of this article is that within the scope of PGSD at the University of Flores, there has never been a psychological examination related to the types of personality traits that can be used as a reference for fostering self-recognition and development of students.